ANALISIS DAYA SAING USAHATANI KOPI LIBTUKOM DI KABUPATEN TANJUNG JABUNG BARAT - Suandi; Handayani, Popy; Muchlis, Fuad (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
After entering the era of free trade in 2015 in the ASEAN Economic Community (MEA) and 2020 around the world through WTO (World Trade Organization) agreement, many things must be considered, each country is required to improve its competitiveness through development in various sectors of the economy especially the goods to be exported to the destination country.The purpose of this research is to analyze the competitiveness of Libtukom Coffea, analyze the impact of government policy on output and input on libtukom coffea farming and analyze competitiveness sensitivity of Libtukom coffea farming to change of output and input. This study uses primary and secondary data sources, to determine the number of respondents calculated by the formula slovin diproleh number of respondents as much as 92 respondents. The data obtained were analyzed using descriptive analysis method and the infractional method by tabulating and processed by using PAM (Policy Analysis Matrix) method. From the result of the research, it can be concluded that: (1) 1) Cultivation of libtukom coffea in Distric of West Tanjung Jabung has comparative and competitive advantage. The use of resources in the research area at the market and international market rates is efficient for economic and financial use as indicated by PCR and DRCR values ​​obtained <1, for PCR obtained 0.195 and DRCR 0.176; (2) In general, local government policies for leather farming still have not shown favorable partiality for small farmers. This can be seen from the result of NPCO value obtained <1 that is equal to 0.912 and seen from NPCI that> 1 is 1.006 and (3) In the simulation of sensitivity done obtained the production costs incurred by each farmer for libtukom coffea cultivation can be covered by the selling price earned.